Pengaruh Pengaruh Model Pembelajaran Elicit, Confront, Identify, Resolve, Dan Reinforce (ECIRR) terhadap Kemampuan Berpikir Kritis dan Keterampilan Proses Sains pada Materi Sistem Ekskresi Manusia Siswa Kelas VIII di SMP Negeri 5 Sungai Bengkal Kabupaten Tebo: The Effect of Elicit, Confront, Identify, Resolve, and Reinforce (ECIRR) Learning Model to Studentâ€™s Critical Thinking Ability and Science Process Skills in the Material of the Human Excretion System for Grade VIII Students at SMP Negeri - Linda Wati; Evita Anggereini; Risnita Risnita (BIODIK, 2023)
This study aims to determine the effect of the ECIRR learning model and discovery learning on students' critical thinking skills and science process skills in grade VIII for the topic human excretion system at SMP Negeri 5 Sungai Bengkal, Tebo Regency. This study used a quantitative approach, through a quasi-experimental method with a pretest posttest only control design. The sample in this study consisted of 60 students divided into 2 class groups, namely the experimental class and the control class. Data collected using observation sheets, tests, interviews, and documentation. The data analysis technique was carried out using two-way analysis of variance with the help of the SPSS Version 21 Program. Based on the results of the research obtained after learning with the ECIRR learning model (experimental class) and discovery learning model (control class). Based on the results of the Multivariate Test, it showed that there was a significant effect because the sig value <0.05 (0.000<0.05) it can be concluded that H0 (rejected) and Ha (accepted). The results of the Test of Between Subjects Effects obtained critical thinking skills of 0.001 <0.05, it can be concluded that H0 was rejected and H1 was accepted and science process skills were 0.001 <0.05, it could be concluded that H0 was rejected and H1 was accepted. So it can be concluded that there is a significant influence on the critical thinking skills and science process skills of students who were taught using the ECIRR learning model with students who who were taught using discovery learning models. Key words: ECIRR learning model, discovery learning model, critical thinking skills & students' science process skills Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran ECIRR dan pembelajaran discovery learning terhadap kemampuan berpikir kritis dan keterampilan proses sains siswa pada materi sistem eksresi manusia kelas VIII di SMP Negeri 5 Sungai Bengkal Kabupaten Tebo. Penelitian ini menggunakan pendekatan kuantitatif, melalui metode Quasi eksperimental dengan desain pretest posttest only control design. Sampel dalam penelitian ini berjumlah 60 siswa dibagi menjadi 2 kelompok kelas, yaitu kelas eksperimen dan kelas kontrol. Teknik pengumpulan data menggunakan lembar observasi, tes, wawancara, dan dokumentasi. Sedangkan teknik analisis data dilakukan dengan Analisis varians dua arah dengan bantuan Program SPSS Versi 21. Berdasarkan hasil uji Multivariate Test menunjukkan terdapat pengaruh yang signifikan karena nilai sig<0,05 (0,000<0.05) dapat disimpulkan bahwa H0 (tolak) dan Ha (terima). Hasil Test of Between Subjects Effects diperoleh keterampilan berpikir kritis 0,001<0,05 dapat disimpulkan bahwa H0 ditolak dan H1 diterima dan keterampilan proses sains 0,001<0,05 dapat disimpulkan bahwa H0 ditolak dan H1 diterima. Jadi dapat disimpulkan Terdapat pengaruh yang signifikan kemampuan berpikir kritis dan keterampilan proses sains siswa yang diajarkan menggunakan pembelajaran model ECIRR dengan siswa yang diajarkan dengan menggunakanÂ  pembelajaran model discovery learning. Kata kunci: Model pembelajaran ECIRR, Model pembelajaran discovery learning, kemampuan berpikir kritis & keterampilan proses sains siswa.